Urban Agriculture and Local Food Systems: A Bibliometric Analysis of Research on Sustainable Cities (West Science Interdisciplinary Studies, 2024)
Urban agriculture and local food systems are pivotal in addressing the challenges of urbanization, food insecurity, and environmental sustainability in modern cities. This study employs a bibliometric analysis to explore the intellectual landscape of research on urban agriculture and its integration into sustainable city frameworks. Using the Scopus database, this study examines publication trends, co-authorship networks, and thematic clusters to identify core research themes, key contributors, and emerging trends. The findings reveal that urban agriculture significantly contributes to food security, climate change mitigation, and community resilience, while also facing challenges such as land scarcity, soil contamination, and economic viability. Policy integration and innovative technologies, including vertical farming and hydroponics, are identified as essential for scaling urban agriculture initiatives. Despite substantial progress, research gaps remain in economic impact analysis, policy frameworks, and digital technology adoption. This study provides valuable insights for researchers, policymakers, and urban planners, emphasizing the interdisciplinary and collaborative efforts required to enhance the role of urban agriculture in sustainable urban development.